Upaya Peningkatan Mutu Pendidikan Madrasah : Studi Kasus MTsN 1 Model Pandeglang dan SMP Mathla’ul Anwar Global School (MAGS) Menes Pandeglang - Anas Nasrudin (CV. Creative Tugu Pena, 2024)
The aim of this research is to identify and analyze: (1) Implementation of content standards at MTsN 1 Pandeglang and SMP Mathla'ul Anwar Global School Menes Pandeglang; (2) Standard implementation process at MTsN 1 Pandeglang and SMP Mathla'ul Anwar Global School Menes Pandeglang?; (3) Implementation of teaching and education staff standards at MTsN 1 Pandeglang and SMP Mathla'ul Anwar Global School Menes Pandeglang. This research is descriptive field research with qualitative analysis, using research instruments: observation, interviews and documentation. The informants in the research are the Madrasah Principal, School Committee, Deputy Principal, Teachers, Administration, and Supervisors who can provide information regarding research problems. The data analysis technique uses data analysis in the form of triangulation of various sources, methods and various times. The conclusion resulting from this research is that there are many similarities in management between content standards, process standards and educational standards at MTsN 1 Pandeglang and SMP Mathla'ul Anwar Global School. For standard content, planning begins by forming a curriculum development team, creating basic curriculum references based on philosophical, juridical and theoretical, developing a curriculum structure, and establishing competency standards based on the National Curriculum, even at Mathla'ul Anwar Global School Middle School for English subjects using Cambridge curriculum.